2004
DOI: 10.1142/s0218810404002054
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Wrist Syndrome Repair

Abstract: Dorsal wrist pain with or without a palpable dorsal wrist ganglion is a common complaint. Watson developed the concept of the dorsal wrist syndrome (DWS) which is an entity encompassing pre-dynamic rotary subluxation of the scaphoid and the overloaded wrist. We reviewed 20 cases of DWS treated surgically. There were nine males (11 wrists) and nine females (nine wrists). Post-operative follow-up ranged from five to 67 months (mean, 37 months). At operation, we observed SLL tears in eight wrists and dorsal gangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…This is supported by Abe et al who found disease in an analogous group of patients through arthroscopy [3,4]. After conservative treatment failed, the second author has operated on these wrist joints; the operation has been previously described [5] but results have not been studied critically.…”
Section: Introductionmentioning
confidence: 79%
“…This is supported by Abe et al who found disease in an analogous group of patients through arthroscopy [3,4]. After conservative treatment failed, the second author has operated on these wrist joints; the operation has been previously described [5] but results have not been studied critically.…”
Section: Introductionmentioning
confidence: 79%
“…The full-text articles for the remaining 109 studies were read and assessed for eligibility, resulting in 11 studies that met the inclusion criteria. 4 5 9 15 16 17 18 19 20 21 22…”
Section: Resultsmentioning
confidence: 99%
“…In 2004, Yasuda et al described 20 cases in which open excision of the dorsal wrist capsules, with excision of the posterior interosseous nerve, was performed; postoperatively, 60% of their patients reported an absence of pain. (9) In a 2008 cadaveric study, Henry proposed that arthroscopic excision of the dorsal wrist capsule was a reliable solution for the treatment of dorsal wrist impingement. (1) In the same year, Wollstein et al published the results of dorsal capsulodesis for radial wrist pain in 88 patients; 80% of their patients described improvement in pain and function, while 25% required further operation.…”
Section: Discussionmentioning
confidence: 99%